2018
DOI: 10.1186/s13098-018-0384-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of vitamin D and vitamin C supplementations with and without endurance physical activity on metabolic syndrome patients: a randomized controlled trial

Abstract: ObjectiveVitamin D and C levels have inverse relation with the metabolic syndrome components and they are used as antioxidant supplements during enduring metabolic activities. In the present study, we hypothesized that the intake of vitamin D and/or C with endurance physical activity might reduce the risk of metabolic syndrome.MethodsA randomized control study recruited 180 participants of both genders, aged between 30 and 50 years. The participants were assigned into six groups receiving different doses of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…Their data concluded that subjects taking vitamin C alone had a lowered TG level compared to placebo. The level of HDL-C was increased, but TG and waist circumference were decreased in MetS patients subjected to vitamin C supplementation with exercise in relative to the placebo [50]. Another randomised double-blind, placebo-controlled trial by the same group of researchers involved 96 MetS patients aged between 30 to 60 years old.…”
Section: The Effects Of Vitamin C Supplementation On Metsmentioning
confidence: 99%
“…Their data concluded that subjects taking vitamin C alone had a lowered TG level compared to placebo. The level of HDL-C was increased, but TG and waist circumference were decreased in MetS patients subjected to vitamin C supplementation with exercise in relative to the placebo [50]. Another randomised double-blind, placebo-controlled trial by the same group of researchers involved 96 MetS patients aged between 30 to 60 years old.…”
Section: The Effects Of Vitamin C Supplementation On Metsmentioning
confidence: 99%
“…Vitamin B7, biotin deficiency has been linked to impaired glucose tolerance, hyperglycemia, and decreased glucose oxidation in animal studies [ 168 ] and a cross-sectional study showed that high levels of vitamin B12 are protective to MetS [ 169 ]. Regarding vitamin C, different patient-based studies have suggested that intake or supplementation decreases the risk of MetS and improves the quality of life of MetS patients [ 169 , 170 ], especially when combined with physical exercise [ 171 , 172 ]. Moreover, a cross-sectional study with more than 2000 patients demonstrated that deficiency of vitamin C was associated with an increased likelihood of MetS [ 169 ].…”
Section: Nutrients (Well-being Through Feeding)mentioning
confidence: 99%
“…Assessment of anthropometric measurements: Height (m), weight (kg), and waist circumference (WC) were measured according to standard [27]. In addition, the body mass index (BMI) was calculated by dividing weight in kilograms by the square of height in meters.…”
Section: Methodsmentioning
confidence: 99%